Kurikulum Pendidikan Agama Islam Di Sekolah Umum - Aisyah Aminy; Dina Latifah; Nurhafifah Maghfiroh Lubis; Nurul Azmi (Al-Ulum: Jurnal Pendidikan Islam, 2020)
Talking about Islamic religious education curriculum is currently starting to develop in various countries. especially in Indonesia, because the majority are Muslims but there are still schools that do not use curriculum related to Islamic religious education, therefore ideas or development are needed for the advancement of Islamic religious education, especially in public schools. The existence of the curriculum has a very significant role in the world of education, that arguably the curriculum is the key in education. This determines the types and qualifications of graduates of an educational institution. The curriculum here we can see the contents are about aqeedah morals, hadith, aquran and fiqh. And siroh (history). Islamic education basically aims to take students to have good aqeedah and good religious depth. This paper looks at how the implementation of PAI curriculum in public schools, the advantages and disadvantages of PAI in schools and the solution of PAI problems in schools.Keywords : Islamic Religious Education, Curriculum, School